The potential applications of fibrin-coated electrospun polylactide nanofibers in skin tissue engineering - Bacakova, Marketa; Musilkova, Jana; Riedel, Tomas; Stranska, Denisa; Brynda, Eduard; Zaloudkova, Margit; Bacakova, Lucie (International journal of nanomedicine, 2016)
Fibrin plays an important role during wound healing and skin regeneration. It is often applied in clinical practice for treatment of skin injuries or as a component of skin substitutes. We prepared electrospun nanofibrous membranes made from poly(l-lactide) modified with a thin fibrin nanocoating. Fibrin surrounded the individual fibers in the membrane and also formed a thin fibrous mesh on several places on the membrane surface. The cell-free fibrin nanocoating remained stable in the cell culture medium for 14 days and did not change its morphology. On membranes populated with human dermal fibroblasts, the rate of fibrin degradation correlated with the degree of cell proliferation. The cell spreading, mitochondrial activity, and cell population density were significantly higher on membranes coated with fibrin than on nonmodified membranes, and this cell performance was further improved by the addition of ascorbic acid in the cell culture medium. Similarly, fibrin stimulated the expression and synthesis of collagen I in human dermal fibroblasts, and this effect was further enhanced by ascorbic acid. The expression of beta1-integrins was also improved by fibrin, and on pure polylactide membranes, it was slightly enhanced by ascorbic acid. In addition, ascorbic acid promoted deposition of collagen I in the form of a fibrous extracellular matrix. Thus, the combination of nanofibrous membranes with a fibrin nanocoating and ascorbic acid seems to be particularly advantageous for skin tissue engineering.
Keywords: proliferace buněk; Regeneration; nanovlákna; Fibroblasts; Collagen; Fibrin; buněčná diferenciace; lidé; tkáňové inženýrství; kolagen; fluorescenční protilátková technika; Fluorescent Antibody Technique; Nanofibers; kůže; messenger RNA; fibroblasty; polymerázová řetězová reakce s reverzní transkripcí; kultivované buňky; Polyesters; extracelulární matrix; regenerace; imunoenzymatické techniky; Humans; RNA, Messenger; Cells, Cultured; Reverse Transcriptase Polymerase Chain Reaction; Skin; Electrochemistry; fibrin; Cell Proliferation; Immunoenzyme Techniques; Extracellular Matrix; Cell Differentiation; Tissue Engineering; polyestery; kvantitativní polymerázová řetězová reakce; Real-Time Polymerase Chain Reaction; elektrochemie